2015
DOI: 10.1016/j.jalz.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Genetically predicted body mass index and Alzheimer's disease–related phenotypes in three large samples: Mendelian randomization analyses

Abstract: Observational research shows that higher body mass index (BMI) increases Alzheimer’s disease (AD) risk, but it is unclear whether this association is causal. We applied genetic variants that predict BMI in Mendelian Randomization analyses, an approach that is not biased by reverse causation or confounding, to evaluate whether higher BMI increases AD risk. We evaluated individual level data from the AD Genetics Consortium (ADGC: 10,079 AD cases and 9,613 controls), the Health and Retirement Study (HRS: 8,403 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 49 publications
5
38
2
Order By: Relevance
“…Observational evidence supports an association with adiposity and AD that varies by age [41] , so, leptin might theoretically be a mediator in the adiposity-AD pathway. However, recent Mendelian randomization analyses found no evidence of a causal association of BMI with AD [42] , and the present study found no causal association of leptin with AD, independent of BMI. Unintentional weight loss is a hallmark of AD [43] , beginning years before the onset of symptoms [44] , so measures of adiposity are expected to be confounders in observational studies examining the relationship between leptin and AD.…”
Section: Discussioncontrasting
confidence: 87%
“…Observational evidence supports an association with adiposity and AD that varies by age [41] , so, leptin might theoretically be a mediator in the adiposity-AD pathway. However, recent Mendelian randomization analyses found no evidence of a causal association of BMI with AD [42] , and the present study found no causal association of leptin with AD, independent of BMI. Unintentional weight loss is a hallmark of AD [43] , beginning years before the onset of symptoms [44] , so measures of adiposity are expected to be confounders in observational studies examining the relationship between leptin and AD.…”
Section: Discussioncontrasting
confidence: 87%
“…We found minimal genetic overlap between BMI and AD. Others have found strong genetic overlap between BMI and AD [53], and yet others found no casual evidence between these traits [57]. These findings suggest that the genetic relationship between AD and BMI and CAD is complex and other factors may be influencing the relationship.…”
Section: Discussionmentioning
confidence: 98%
“…Unlike that study, we did not create separate polygenic risk scores from a GWAS of another phenotype, but grouped genome-wide significant predictors of T2D and associated genes into biologically functional groups that contribute to the expression of the T2D phenotype, following our prior approach with other heterogeneous phenotypes, such as body mass index. 35 The “insulin sensitivity” group in our study consists of nine SNPs presumed on the basis of physical proximity to represent genes whose functions influence insulin sensitivity. Although some of the SNPs are related to genes that were also included in Oestergard's insulin resistance polygenic score (Insulin Receptor Substrate 1 (IRS1), Peroxisome Proliferator-Activated Receptor Gamma (PPARG), they were rescaled in the current paper according to their association with T2D.…”
Section: Discussionmentioning
confidence: 99%